Priprava notranjih pravil v podjetju Mariborski vodovod d. o. o. - Androić, Sanja (Moderna arhivistika, 2022)
Maribor Water Supply Company received confirmation of the Internal Rules for the Capture and Storage of Digital Records in 2020 and thus provides legally compliant digital storage and legal validity of stored digital and digitized records. Internal rules are valid for the field of received and issued invoices, records of the purchase procedure and records of the company's outbound, received and internal mail. Internal rules provide safe storage of mentioned digital documents. However, all defined procedures must be followed: from receiving records, their digitization, recording, monitoring quality of capture and traceability, to archiving, monitoring backup copies and documenting. Key advantages of e-business encompass lesser storage space, less paper and greater care for the environment, more efficient procedures, faster searching and greater satisfaction of clients and business partners. There are some disadvantages: complicated legislation, higher costs of technology, information safety and education of employees, higher costs of external advisors. The field of e-processes, e-records and e-storage is complicated and demands great care and responsibility on the employees' side. The article presents challenges of preparing internal rules from the practical point of view, which will help companies deciding to approach this task.
Keywords: e-business; e-hramba; e-poslovanje; e-procesi; e-processes; e-storage; internal rules; Maribor Water Supply Company; Mariborski vodovod; notranja pravila